'Distance travelled versus the 'distance' travelled': Enhancing the student learning experience using a creative and innovative approach to tutorial organisation - Simon Peter Brownhill (Association for Learning Development in Higher Education (ALDinHE), 2014)
In an effort to remain both competitive and attractive to prospective and established students Higher Education institutions, both at a national and international level, are actively seeking innovative ways 'of improving the student experience and student progression/retention' (National Audit Office, 2002 in Stevenson, 2009, p. 117). This paper reports on an original approach to tutorial organisation to enhance the learning experience of undergraduate students on a practice based foundation degree at a UK university. Students' perceptions of tutorials prior to and post their active engagement with a Tutorial Stations system (TSS) within the classroom learning space will be shared and discussed. Whilst there is student calling to sustain usage of the system as part of other taught modules on the programme further research is needed to evaluate the impact of the system on improving student attainment.